Digitalization and the welfare state - Busemeyer, Marius R. 1978-; Kemmerling, Achim; Marx, Paul 1982-; Kersbergen, Kees van 1958- (Oxford University Press, 2022)
This volume explores how digitalization - in different forms - affects the welfare state. Digitalization is likely to have a lasting impact on work, welfare, and the distribution of income. The volume studies how digitalization affects policies as well as the underlying power relationship between actors, i.e. the politics of the welfare state
Keywords: Digitalisierung; Neue Technologie; Wohlfahrtsstaat; Konferenzschrift -- 2019